Fenton’s Oxidation to Improve the Filterability and Dewaterability of Excess Activated Sludge by Affecting Extracellular Polymeric Substances - Ye, Fenxia; Peng, Ge; Li, Ying (Asian Journal of Chemistry, 2014)
This paper investigated the effect of Fenton's reagent pretreatment on the filterability and dewaterability of the excess activated sludge. Fenton's reagent pretreatment greatly improved the filterability and dewaterability of the sludge measured by the capillary suction time (CST) and moisture of sludge cake, respectively. The suitable conditions of Fenton pretreatment on the sludge filterability were as following: pH 2.5-3.0; 60-70 °C; treatment time of 2-3 h. The filterability and dewaterability of the sludge increased by 81 and 12 %, respectively, at pH 2.5 under 68 °C for 2.5 h reaction time when the sludge was treated by Fenton reagent with H2O2/Fe2+ ratio of 8. There was no significant difference in the filterability and dewaterability at various ratios of H2O2/Fe2+. The contents of loosely bound extracellular polymeric substances (EPS) (LB-EPS), tightly bound EPS (TB-EPS), polysaccharides (PS) in LB-EPS, PS in TB-EPS and proteins (PN) in TB-EPS all reduced, but protein content in LB-EPS increased after Fenton's pretreatment. Protein in TB-EPS was strongly correlated with capillary suction time and moisture of sludge cake. A significant reduction of extracellular polymeric substances concentration was the major reason for the observed changes in the sludge filterability and dewaterability.